2004
DOI: 10.1007/s00425-003-1125-1
|View full text |Cite
|
Sign up to set email alerts
|

Electron tomographic analysis of post-meiotic cytokinesis during pollen development in Arabidopsis thaliana

Abstract: The mechanism of cell wall formation after male meiosis was studied in microsporocytes of Arabidopsis thaliana (L.) Heynh. by means of thin-section and immuno-electron microscopy and dual-axis electron tomography of high-pressure-frozen/freeze-substituted cells. The cellularization of four-nucleate microsporocytes involves a novel type of cell plate, called a post-meiotic-type cell plate. As in the syncytial endosperm, the microsporocyte cell plates assemble in association with mini-phragmoplasts. However, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 40 publications
1
102
0
Order By: Relevance
“…The darkstained vesicles were also found in the vicinity of the Golgi apparatus, and it was concluded that they were Golgi derived. Prevacuolar compartment/multivesicular bodies (MVBs) or late endosomes were detected around the cell plate at its maturation phase, accompanied by an increased appearance of clathrin-coated vesicles (Otegui et al, 2001;Otegui and Staehelin, 2004;Segui-Simarro et al, 2004;Segui-Simarro and Staehelin, 2006). The observation that Arabidopsis (Arabidopsis thaliana) Golgi stacks double before mitosis (Segui-Simarro and Staehelin, 2006) supports the capacity for substantial vesicle secretion during plant cytokinesis.…”
Section: Origin Of Cell Plate-building Vesiclesmentioning
confidence: 89%
See 2 more Smart Citations
“…The darkstained vesicles were also found in the vicinity of the Golgi apparatus, and it was concluded that they were Golgi derived. Prevacuolar compartment/multivesicular bodies (MVBs) or late endosomes were detected around the cell plate at its maturation phase, accompanied by an increased appearance of clathrin-coated vesicles (Otegui et al, 2001;Otegui and Staehelin, 2004;Segui-Simarro et al, 2004;Segui-Simarro and Staehelin, 2006). The observation that Arabidopsis (Arabidopsis thaliana) Golgi stacks double before mitosis (Segui-Simarro and Staehelin, 2006) supports the capacity for substantial vesicle secretion during plant cytokinesis.…”
Section: Origin Of Cell Plate-building Vesiclesmentioning
confidence: 89%
“…Indeed, ultrastructural analysis has revealed a close association of vesicles with the phragmoplast microtubules (Kakimoto and Shibaoka, 1987;Samuels et al, 1995), the integrity of which is essential for cell plate vesicle delivery (Steinborn et al, 2002). Proteins connecting vesicles to phragmoplast microtubules have been visualized during endosperm cellularization and pollen cytokinesis (Otegui et al, 2001;Otegui and Staehelin, 2004). The kinesin AtPAKRP2 is so far the best candidate motor protein to transport the cell plate-building vesicles to the division plane (Lee et al, 2001), although genetic data for this are lacking.…”
Section: Origin Of Cell Plate-building Vesiclesmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitution and subsequent embedding of samples in Epon resin (Ted Pella) were carried out as described previously by Otegui and Staehelin (2004). Eighty-to 100-nm sections were cut and stained with uranyl acetate (8% in 50% ethanol) and Reynolds lead citrate (Reynolds, 1963) before imaging with a CM120 transmitting electron microscope (Philips).…”
Section: Visualization Of Pollenmentioning
confidence: 99%
“…Electron tomography, which is a powerful electron microscopic technique for getting a nano-scale three-dimensional analysis, has been used in the ultrastructural studies of cytokinesis of land plants (Otegui and Staehelin 2004, Segui-Simarro et al 2004, Haas and Otegui 2007. This technique will be also useful for analysis of tiny PD structure, in order to investigate their ultrastructure and the process of their formation.…”
Section: Introductionmentioning
confidence: 99%